Extreme Heat Impacts on the Viability of Alternative Transportation for Reducing Ozone Pollution: A Case Study from Maricopa County, Arizona - Braun, Rachel A.; Fraser, Matthew P. (Weather, climate, and society, 2022)
One commonly proposed strategy for reducing urban air pollution is transitioning from single-occupancy vehicle (SOV) travel to alternative transportation (AT) modes, such as walking, biking, and using public transportation. While many studies have addressed the benefits of switching from SOV to AT, fewer studies have examined the potential for negative outcomes due to increased exposure to heat when using AT modes. This work uses Maricopa County, Arizona, home to the metropolitan Phoenix area, as a test case to examine the potential impacts of heat on commuters who utilize AT. First, regions of the county with the most candidates for switching from SOV to AT were identified and used to develop an AT candidate index. This index was based on both the current rates of AT use and the number of SOV commuters with the shortest commuting times in the dataset (<10 min). Next, typical weather conditions during warnings for high ozone (O₃) pollution were examined. From 2017 to 2020, over one-quarter of all days with an O₃ warning also were subject to an excessive heat warning. Last, land surface temperature data were used to determine the potential for increased heat exposure during AT commuting at both the ZIP code and AT infrastructure (public transit stops and bikeways) scales. Although this work focuses on Maricopa County, the issues presented here are increasingly relevant for cities across the world that are subject to poor air quality, hotter temperatures, and heat waves.